Analisis Tingkat Kepuasan Pasien Rawat Inap Terhadap Kualitas Pelayanan Gizi di RSD Idaman Banjarbaru - Yustin Prihandini; Cast Torizellia; Adies Riyana; Nadia Susiana (Universitas Malahayati Lampung, 2024)
ABSTRACT Nutrition services in hospitals are one of ten facilities and services that must be available in hospitals. Identifying the description of respondents in terms of age, gender and occupation as well as a description of the quality of service at the inpatient hospital at Idaman Banjarbaru Hospital. This type of research is descriptive observational. The sample in this study was 60 inpatients at Idaman Hospital, Banjarbaru City. The sample in this study used an accidental sampling technique. Measuring tools/instruments with questionnaires distributed to the sample. Inpatients Have a High Level of Satisfaction with the Quality of Nutrition Services at RSD Idaman Banjarbaru. Keywords: Gizi, Pelayanan, Rumah Sakit ABSTRAK Pelayanan Gizi di rumah sakit adalah satu dari sepuluh fasilitas dan pelayanan yang harus ada di rumah sakit. Mengidentifikasikan gambaran responden dari segi umur, jenis kelamin, dan pekerjaan serta gambaran kualitas pelayanan di rawat inap RSD Idaman Banjarbaru. Jenis penelitian ini adalah observasional yang bersifat deskriptif, Sampel dalam penelitian ini adalah 60 pasien rawat inap di RSD Idaman Kota Banjarbaru. Sampel dalam penelitian ini menggunakan teknik accidental sampling Alat ukur / Instrumen dengan kuesioner yang disebar pada sampel. Pasien Rawat Inap Memiliki Tingkat Kepuasan Yang Tinggi Terhadap Kualitas Pelayanan Gizi Di RSD Idaman Banjarbaru Kata Kunci: Nutrition, Service, Hospital